Ureditev postopka osebnega stečaja po noveli ZFPPIPP-H - Lajevec, Maja (Podjetje in delo, 2023)
The amendments to the Financial Operations, Insolvency Proceedings, and Compulsory Dissolution Act (ZFPPIPP-H) are also addressing personal bankruptcy and debt discharge, as well as introducing new regulations regarding inheritance bankruptcy. The main purpose of these changes is to eliminate inconsistencies from previous amendments, align the process with decisions of the Constitutional Court and the Directive on restructuring and insolvency, improve creditor repayment, encourage greater debtor involvement during the trial period, and provide more precise formulations of specific rules that have been interpreted differently in practice. However, the position of creditors in personal bankruptcy is not significantly improved by this amendment. The changes that enhance the debtor's position outweigh the additional requirements imposed on them by the amendment. Therefore, creditors will have to monitor the considerably improved debtor position within the scope of their unchanged powers.
Keywords: dolžniki; finančno poslovanje; insolventnost; novele zakonov; podjetja; pravna ureditev; stečaj; upniki